The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/ol.2016.5155
|View full text |Cite
|
Sign up to set email alerts
|

Primary mesenchymal tumors of the pancreas in a single center over 15 years

Abstract: Abstract. In total, 95% of primary tumors in the pancreas are epithelial tumors; primary mesenchymal tumors at this site are extremely rare. At present, only one comprehensive study about these rare tumors has been performed. Another retrospective analysis of these rare tumors is performed in the present study, which, to the best of our knowledge, is the first to be performed in China. In the present study, 10 patients that underwent resection for primary mesenchymal tumors of the pancreas were identified in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…and Kim et al. it was found that desmoid tumor was the most common benign mesenchymal pancreatic tumor, followed by solitary fibrous tumor [3] . The mean age of presentation is 36 years old and there is slight female to male predilection for abdominal DTs [4] .…”
Section: Discussionmentioning
confidence: 92%
“…and Kim et al. it was found that desmoid tumor was the most common benign mesenchymal pancreatic tumor, followed by solitary fibrous tumor [3] . The mean age of presentation is 36 years old and there is slight female to male predilection for abdominal DTs [4] .…”
Section: Discussionmentioning
confidence: 92%
“…The pancreatic origin DT remains an extremely rare subset of DTs. The English literature from the 1980s report 27 pancreatic DTs, and therefore our case is case number 28th [1] , [2] , [4] , [5] , [11] , [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Presenting symptoms of primary pancreatic leiomyosarcomas may include abdominal pain, abdominal mass, weight loss, and jaundice, although the diagnosis is usually incidental [ 1 , 5 , 6 ]. Pancreatic leiomyosarcomas may be located in the pancreatic head, body, or tail [ 1 , 5 ]. These tumors are usually large in size at presentation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primary mesenchymal tumors of the pancreas are rare, with only 221 cases reported to date [ 1 ]. Primary pancreatic leiomyosarcomas are an even rarer subtype, with only 69 reported cases to date [ 2 ].…”
Section: Introductionmentioning
confidence: 99%